Addressing racism and restoring justice: A theatre and education-based approach to community mental wellness. Issue 1 (1st July 2022) - Chamblin, Michelle; Sarju, Shalinie; Wood, Laura L.; Uddin-Schmidt, Nafeeza
This mixed-methods study explored the impact of a theatre-based community mental health and education initiative to address racism. Comparisons were examined between participants who either just saw a musical that centred on the theme of racism, or who saw the same musical and partook in a post-show experiential workshop that used restorative justice practices and drama therapy/applied theatre exercises. The results established that participants who saw the show and attended the post-show workshop (n = 38), in comparison to participants who only saw the show (n = 69), significantly (p = .001) agreed that the combined experience allowed them to reflect on biases and other forms of discrimination. Researchers also discovered that age and gender yielded considerable differences across groups. Additionally, there were five themes that were derived from the applied thematic analysis. Participants reported: (1) increased knowledge; (2) that they felt emotions; (3) that they connected with others; (4) that they experienced personal transformation in the here and now; and (5) that they were inspired to enact change. These qualitative themes supported quantitative analysis, which concluded that, while the theatre experience alone was impactful, the workshop augmented the central message and cultivated participants' deeper reflections.